A Report on the Excavation at the Mala Mcha Graveyard, Kurdistan, Iran. Issue 2 (3rd July 2017) - Amelirad, Sheler; Mohajerynezhad, Abdolreza; Javidkhah, Masoume
ABSTRACT: The Mala Mcha graveyard is located in Iranian Kurdistan, near the ancient Mannaean site of Ziwiya. Abdolreza Mohajerynezhad and Rasol Oshtodan conducted rescue excavations at Mala Mcha in 2012, and 16 graves were uncovered. Although most of the graves had been plundered by tomb robbers the tomb structures, and especially the grave-goods that remained, suggest an Iron Age III date and close relations with neighbouring sites such as Ziwiye, Qalaichi and Changbar. Most of the graves were covered with large flat slabs and contained one, two or three burials, the exception being tomb no. 7 with 14 burials.